A doll's house - Ibsen, Henrik, 1828-1906.; Meyer, Michael; Worrall, Nick.; Worrall, Non. (London : Methuen Drama, 2008)
Presents Ibsen's 1879 play in which Nora, stifled as a pampered wife, forges a signature to obtain money for her ailing husband, resulting in her personal growth and increased resentment of being treated like a doll in her own home; and includes a chronology of Ibsen's life and work, a plot summary, commentary, and other reference information.
Translation of: Dukkehjem.
Includes bibliographical references.
Adult.
Adult
Keywords: Marriage -- Drama; Middle class -- Drama; Marriage -- Drama; Middle class -- Drama